Economia solidária : ideologia no cotidiano do trabalho associado - Leitão, Alexander Chagas (2018)
The urgency of capitalism to grow and feed itself has in the exploitation of labor one of its main pillars. Suffocated by "having" and not by "being," contemporary society seeks to fit into a pattern through alienated consumption, stirring up the Social Question. In the process of strengthening the counter-hegemony of capital, there are actions that seek alternative forms of employment and income generation, aiming at social justice, cooperation and isonomy at work through the Politics of Solidarity Economy. Operationalised by associative and cooperative work processes, there are two fundamental characteristics in its structure of action: the formation process and the self-knowledge of the subject. These components are fundamental for the establishment of the critical awareness of the associated worker, besides constituting the ideological referential in their daily life. Thus, this research sought to understand how the associated work processes are developed through the ideological references that emerge in the daily life of the Solidary Economy. For this, the study had guiding categories, such as the history and trajectory of the subject, their participation, training processes and the impacts of daily life on the associated work. The theoretical foundation was established for the understanding of Ideology, through the critical social theory of John B. Thompson (1995), Daily Life, Agnes Heller's Theory of Daily Life (2008), with theoretical references on Education, Work and Economics Solidary. It was a qualitative research, through case studies, using the method of historical and dialectical materialism. As research instruments, an open interview was used. This research was developed by an intentional sample with three women, with the following criteria: representatives of the associated work that were guided by the Politics of Solidarity Economy, where each one had at least five (05) years of trajectory, with the sample of the intentional type , one (01) subject per interview. The data treatment was carried out through discursive practices (discourse analysis), through Spink Narrative and Sense Production (2004). The research evidenced that the Solidarity Economy can be a public policy strengthening the associated worker, with criticism by the methods of formation like the popular education and extension of the knowledge, even being the shadow of the capitalist State in opposition to this policy, resulting in contradiction and decline as in the current scenario. It is in everyday life that the Solidarity Economy has greater significance, because daily actions bring conflicts, such as the duality between heterogestion and self-management, a process of contradiction where the subjects can be perceived in their work processes, leading to a social emancipation.